From Husserl to Levinas: The Role of Hyletic Data, Attachment, Emotion and the Other in Temporality - Poleščuk, Irina (Problemos, 2009)
This article discloses the question of the pre-giveness of the other and alterity by analyzing and comparing the temporality of consciousness and the role of affection and sensation in Husserl and Levinas. I argue that within the intentional flow of consciousness one can find non-intentional structures, i.e. affection and hyletic data which mark a passivity of consciousness, break intentional act and welcome the other. While discussing the temporal structure of consciousness the special attention is given to the discussion of pra-impression.